DEBATING THE SCIENCE OF JURISPRUDENCE; STUDYING JURISPRUDENCE FROM PHILOSOPHY OF SCIENCE PERSPECTIVE (International Conference on Social and Islamic Studies, 2021)
The article discusses jurisprudence in terms of the philosophy of science; so far, there have been doubts in the study of jurisprudence due to the object, whether jurisprudence is included in science or only knowledge of legislation. In discussing jurisprudence, the author uses literature search methodology (library research) using the Philosophy of Science approach, specifically Epistemology, Ontology, and Axiology. The Philosophy of science approach will reveal the meaning of science on Jurisprudence